Relationship between tumor viability during treatment and the clinical outcomes of patients with bladder/prostate rhabdomyosarcoma: a single-center experience - Li, Yun-Peng; Song, Hong-Cheng; Ma, Xiao-Li; He, Le-Jian; Zhang, Wei-Ping (The Turkish Journal of Pediatrics, 2021)
Background. To analyze the relationship between tumor viability in specimens retrieved at second-look procedures (SLPs) and clinical outcomes in patients with bladder/prostate rhabdomyosarcoma (BP RMS). Methods. We retrospectively analyzed patients` characteristics, times between diagnoses and SLPs, types of SLPs, the pathological findings, and clinical outcomes between January 2003 and May 2014. Results. A total of 29 patients underwent at least one SLP before completing chemotherapy, including 24 boys and 5 girls. The mean age was 36 months. No patients with clinical/radiographic complete responses (CRs) had viable tumor cells and 7/18 patients (38.9%) without CR had no viable tumor cells. Seven patients experienced tumor relapse, progression, and metastasis, and three of these survived. Five-year event-free survival (EFS) rates were 88.5% in 18 patients without viable tumor at SLPs and 54.5% in 11 patients with viable tumor (Cox proportional hazards adjusted P=0.045). The respective five-year overall survival (OS) rates were 94.1% and 72.7% (Cox proportional hazards adjusted P=0.175). Conclusions. EFS was increased in patients with BP RMS having no viable tumor cells; however, OS was comparable in patients with and without viable tumor cells. Patients who achieved CR during the treatment generally had no viable tumor cells.
Keywords: bladder/prostate; outcome; rhabdomyosarcoma; second-look procedures